(untitled) (Physical Education, Health and Social Sciences, 2026)
Background: Obesity defined as BMI of more than 40 kg/m2 is a major health concern which is attributed to a range of complications such as cardio metabolic diseases, DM, and metabolic disorders affecting the skeletal structures. Some of these health problems must be linked to hormonal problems and older age, which is why postmenopausal women are more at risk. Learning about how severe obesity affects their health and movement is informative in the development of strategies for management of their conditions; they need a better lifestyle. Objective: The present research is aimed at assessing the influence of obesity and CV parameters on the spine and gait problem in the PMW. Methods: It is important to note that this is a cross-sectional study, in which quantitative data from 120 participants was collected, and checked for obesity-related health conditions, FGA scores and physical activity. Results: The analysis exposes poorer peripheral artery disease, cardiovascular diseases, and diabetes mellitus health people suffering from severe obesity. Furthermore, the sedentary behavior and Functional mobility also diminished in this population. Conclusion: Based on this, this study found that persons with severe obesity experience aggravated health and functional deficits. Investigations have shown that this population has a greater prevalence of peripheral artery disease, cardiovascular diseases, and diabetes mellitus with reduced physical activity levels and impaired mobility. Such findings highlight the dire necessity for proper and individualized interventions for patients which would include the management of weight, increments in physical activity levels, and the like.